2021
DOI: 10.1111/apt.16485
|View full text |Cite|
|
Sign up to set email alerts
|

One‐quarter of chronic hepatitis D patients reach HDV‐RNA decline or undetectability during the natural course of the disease

Abstract: Background: Spontaneous HDV-RNA fluctuations, assessed by nonstandardised inhouse assays, have been reported during the course of chronic hepatitis delta (CHD).Aims: To evaluate changes in serum HDV-RNA concentrations in untreated CHD patients and correlate these changes with other HBV markers.Methods: A total of 323 consecutive serum samples from 56 CHD patients (detectable HDV-RNA) followed for >3 years were retested for HDV-RNA levels by a sensitive technique using the first WHO international HDV-RNA standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
(59 reference statements)
2
24
1
Order By: Relevance
“…[2][3][4] Support for a milder CHD course is described recently in Alimentary Pharmacology and Therapeutics. In that study, Palom et al 5 report a retrospective multicentre study on a CHD cohort of 56 patients with compensated liver disease followed longitudinally for a mean duration of 5.6 (3-16) years. Two-thirds were on nucleos(t)ide analogue (NA) treatment.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…[2][3][4] Support for a milder CHD course is described recently in Alimentary Pharmacology and Therapeutics. In that study, Palom et al 5 report a retrospective multicentre study on a CHD cohort of 56 patients with compensated liver disease followed longitudinally for a mean duration of 5.6 (3-16) years. Two-thirds were on nucleos(t)ide analogue (NA) treatment.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…However, this study mainly aimed to analyze the HBV RNA trend over time and its association with HBV DNA. To facilitate this purpose, we converted DNA test results from IU/mL to copies/mL using the conversion factor of 5.82 ( 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…64 Spontaneous fluctuation of both HBV and HDV viral markers has also been observed, and a recent retrospective study of untreated HDV patients showed that one-quarter of them achieved a spontaneous HDV RNA decline associated with HBsAg and HBV DNA decreases. 71 Clinical details of HDV infection are summarised in Table 1 and Figure 4.…”
Section: Natural Historymentioning
confidence: 99%